Epromoters function as a hub to recruit key transcription factors required for the inflammatory response - David Santiago-Algarra (Nature Portfolio, 2021)
Some promoters, termed Epromoters, can display enhancer activity and regulate distal genes in their endogenous context. Here the authors report the broad involvement of Epromoters in the coordinated activation of interferon (IFN) response. They show activation of a number of IFN-inducible genes is a result of Epromoters regulating expression of an entire IFN response gene cluster.